TECHNOLOGY TRANSFER: AN INTERDISCIPLINARY PROCESS - Nádia Solange Schmidt Bassi; Christian Luiz da Silva; Alain Hernández Santoyo (European Scientific Journal, ESJ, 2015)
This article describes the importance of technology transfer process (TT) for public research institutions and its necessity to be planned from a research project design. It also presents a comparative analysis of technology transfer process between the Brazilian Agricultural Research Enterprise (Embrapa) and the Agricultural Research Service (ARS). Therefore, a descriptive study was conducted with the use of printed and electronic documents. Interviews were also developed with employees associated to this process in strategic and operational levels for both institutions. Results demonstrate that both institutions rely on a structured TT process. However, this process is more effective in ARS than at Embrapa. One of the most probable causes supports that the research model used in ARS is the reverse linear model (demand pull), which considers market demands in the development of research projects, while Embrapa works with the research linear model, where TT process begins only after obtaining the research result. The papers suggests, in order to make the TT process more effective, Embrapa could consider the demands of its targets audience and planning the TT actions where elaborating its projects conjoint.